Aplikasi Kompos Tandan Kosong Kelapa Sawit (TKKS) terhadap Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo. L) - Friskia Hanatul Qolby; Hary Ardian Sebayang (Mahesa Research Institute, 2023)
One of the fruits favored by the community is melon (Cucumis melo. L), which is classified as a horticultural commodity. Melon has prospects for cultivation because it contains many vitamins and benefits. This research was carried out in August - December 2019 in Limau Manis Village, Pauh District, Padang City. The research method is an experimental method using a completely randomized design (CRD) with 4 treatment levels and 5 replications. The level of treatment given was the dose of OPEFB compost 10, 20, 30, 40 tons/ha. Observational data were analyzed statistically with the F test at the 5% level. The results of the analysis of variance were continued with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that the application of oil palm empty fruit bunches compost at a dose of 30 tons/ha had the best effect on the growth of height and stem diameter of melon plants. However, the application of oil palm empty fruit bunches compost at doses of 10, 20, 30, and 40 tons/ha has not been able to have a significant effect on melon crop production.